Penerapan Sistem Informasi Akuntansi pada Perusahaan PT Citra Jelajah Informatika (Cifo Group) - Alisa Yulistina; Yulia Eka Cahyani; Zyhan Hardiyani; Mohamad Rifki Yusup; Asti Purnama Sari (Pusat Riset dan Inovasi Nasional, 2025)
This study examines the implementation of the Accounting Information System at PT Citra Jelajah Informatika (CIFO GROUP), which aims to evaluate the effectiveness of the system in supporting the company's business processes. With a qualitative approach and case study method, data were obtained through interviews, observations, and document analysis. The results of the study indicate that although the accounting information system being developed has the potential to improve operational efficiency, there are significant obstacles, such as the length of the funding application process and the lack of integration between functions. The accounting system implemented is not yet fully optimal, so it requires improvement to improve the effectiveness and accuracy of financial reporting. The separation of functions between sales, finance, and accounting needs to be strengthened, and the use of formal documents such as invoices and receipts is very important to maintain transparency. By implementing the proposed improvement suggestions, it is hoped that PT Citra Jelajah Informatika can improve the performance of the accounting information system and support the company's future growth